Campaign Finance Laws, Policy Outcomes, and Political Equality in the American States. (March 2015) - Flavin, Patrick
Laws that regulate the financing of campaigns are one attempt to attenuate the role of money in politics and promote more egalitarian policy outcomes. Do states with stricter campaign finance regulations represent citizens' interests more equally? Using data on state spending priorities from 1977 to 2008, this article finds that states with stricter campaign finance laws devote a larger proportion of their annual budget to public welfare spending in general and to cash assistance programs in particular. In contrast, there is no relationship between the strictness of campaign finance laws and spending decisions for non-redistributive policy areas. I also investigate possible causal mechanisms and uncover evidence that stricter campaign finance laws alter incentives for candidates to respond to wealthy constituents by lessening the proportion of contributions that originate from business interests. These results suggest that laws that regulate the financing of political campaigns can play an important role in promoting the interests of disadvantaged citizens and enhancing political equality.